Implementation of Two-Way Voice and Text Communication System Using Fiber Optic Media - Hendro Darmono; Simon Calvin Pribadi; Yoyok Heru Prasetyo Isnomo (Politeknik Negeri Malang, 2022)
In this technology age, people's need for communication systems is growing. In various places and conditions, communication must be maintained to meet various needs. One of the solutions required in these circumstances is an optical fiber communication system. Fiber optic cable is a light-based data transmission technique. The advantages of optical transmission include the fact that the light spectrum does not spread like radio frequencies, making it impossible to intercept, the fact that it propagates at a very high speed, allowing it to go very large distances, and the ease with which it may be installed. To tackle this problem, we proposed to innovate by realizing and developing a two-way voice and text communication system using fiber optic cable media. The voice and text communication system created and deployed in this study is based on an Android application. This communication system does not require a server and internet network. Only Android smartphones, access points, fiber media converters, and fiber optic cables are required. The greatest throughput value measured by the system is 2708 bytes/second, while the lowest is 1020 bytes/second. The longest delay is 2.314 seconds, while the shortest is 1.99 seconds. In terms of packet loss, the value is 0%.